Алгебраїчна школа професора Дмитра Граве - Тіт, О.; Шоха, Володимир Петрович (My University, 2014)
Наукова та педагогічна діяльність Дмитра Олександровича Граве мала великий вплив на розвиток математики не лише в Україні та СРСР, але й в усьому світі. Research and teaching activities Dmitry Aleksandrovich Grave had a great influence on the development of mathematics not only in Ukraine and the Soviet Union, but also worldwide.
Keywords: Граве Дмитро; математик; кафедра вищої математики імені проф. Можара В. І.